Diffusion coefficients of trivalent rare earth/actinide ions in acid and alkaline aqueous solutions - Liyana Nadirah, M. S.; Deraman, M. R.; Wan Ibrahim, W. H.; Harun, N. (IOP Publishing Ltd, 2019)
Leaching is one of the key process of rare earth (RE) element recovery. This paper was set out to validate the effectiveness of acid/alkali in RE leaching by measuring the limiting ionic conductivity (λo), self-diffusion coefficient (Di) and overall diffusion coefficient (DAB) to obtain a clear insight on the transport properties of ions and salts in aqueous solution. The calculation diffusivity of Di which is diffuse individual ions in pure water and DAB diffuse in chemical reagents were determined using Nernst-Haskell equation, applicable for 25°C. The results of D i were found to be consistent with experimental data from the literature where most of calculation and experiment data are less than 5% error. The final outcome had managed to confirm that NaOH is best reagent for most RE element leaching, which suits the common practice of the industry.